Analisis Desain Sampul Novel Karangan Ayu Utami Ditinjau Dari Perspektif Desain Komunikasi Visual - Hasian, Irene (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2017)
Novel in Indonesia became a popular reading, one by novelist Ayu Utami. However, it turns out Ayu Utami create her own cover design of her novels. Writer interested to examine how to determine the cover design visualization contained in Ayu Utami’s novel that affect she make their own novel’s cover. The method used in this study include observational data collection, interviews, and literatures. The results of the study began seeing Ayu Utami’s novels that tell about the history, culture, sex and myths. In addition to getting entertainment, reading novels Ayu Utami also could add insight and information about the history and culture that has not been known. Each novel is written always do research beforehand. Almost the entire cover of the novel made by Ayu Utami. Researchers then describe what elements are there in Ayu Utami covers novel, includes illustrations, color, typography, and layout, and then analyze it. Conclusions from this research that works Ayu Utami’s novel illustrations is not entirely explanation contents story, but it contains meanings associative relationship exciting to be a conceptual work.